Progressive Legal Views on the Implementation of the Omnibus Law Method in Indonesia - Nynda Fatmawati Octarina; Priskila Fransisca Haryono; Elisabeth Yulia Rana; Muhammad Fahmi; Abdullah Abdullah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Indonesia is a constitutional state which was contain in Article 1 paragraph (3) of the 1945 Constitution of the Republic of Indonesia and based on the prevailing laws and regulations. The current laws and regulations are considered to have a lot of influence on legal positivism teachings, the law is considered rigid and causes the number of regulations that Indonesia has. The number of regulations is considered quite a cause for concern, and can lead to a decline in the quality of regulations in Indonesia. So, the Government tries a new method, namely the omnibus law method in simplifying regulations in Indonesia. The government's efforts to reduce regulatory obesity through the omnibus law method are considered formal flaws because they are not in accordance with the rules for the formation of laws and regulations stipulated in Law no. 12 of 2011. The progressive legal view of the omnibus law is necessary then to see the real and living substantial aspects of society and the consideration of social perspectives needs to be adjusted and the Government needs to continue to explore the real aspects in society.